Classification of Proteus vulgaris biogroup 3 with recognition of Proteus hauseri sp. nov., nom. rev. and unnamed Proteus genomospecies 4, 5 and 6. - C M O'Hara; Frances W. Brenner; A G Steigerwalt; Bertha C. Hill; B. Holmes; Patrick A. D. Grimont; Peter M. Hawkey; J L Penner; Miller Jm; D J Brenner (2000)
Strains traditionally identified as Proteus vulgaris formed three biogroups. Biogroup 1, characterized by negative reactions for indole production, salicin fermentation and aesculin hydrolysis, is now known as Proteus penneri. Biogroup 2, characterized by positive reactions for indole, salicin and aesculin, was shown by DNA hybridization (hydroxyapatite method) to be a genetic species separate from biogroup 1 and from biogroup 3 which is positive for indole production and negative for salicin and aesculin. In this study, 52 strains were examined, of which 36 strains were Proteus vulgaris biogroup 3, which included the current type strain of the species P. vulgaris (ATCC 29905T), and compared to seven strains of Proteus vulgaris biogroup 2 and nine type strains of other species in the genera Proteus, Providencia and Morganella. By DNA hybridization, these 36 strains were separated into four distinct groups, designated as Proteus genomospecies 3, 4, 5 and 6. DNAs within each separate Proteus genomospecies were 74-99% related to each other in 60 degrees C hybridization reactions with < or = 4.5% divergence between related sequences. Proteus genomospecies 3 contained the former P. vulgaris type strain and one other strain and was negative in reactions for salicin fermentation, aesculin hydrolysis and deoxyribonuclease, unlike the reactions associated with strains considered as typical P. vulgaris which are positive in reactions for salicin, aesculin and DNase. Genomospecies 3 can be distinguished from Proteus genomospecies 4, 5 and 6 because it is negative for Jordan's tartrate. Proteus genomospecies 4, containing five strains, was differentiated from Proteus penneri, genomospecies 3 and 6 and most, but not all, strains of genomospecies 5, by its ability to ferment L-rhamnose. Proteus genomospecies 5 and 6, containing 18 and 11 strains, respectively, could not be separated from each other by traditional biochemical tests, by carbon source utilization tests or SDS-PAGE of whole-cell proteins. In an earlier publication, a request was made to the Judicial Commission that the former type strain of P. vulgaris (ATCC 13315) be replaced by P. vulgaris biogroup 2 strain ATCC 29905T, a strain considered more biochemically typical of P. vulgaris strains. This would have the effect of assigning the name P. vulgaris to P. vulgaris biogroup 2. Since this request has been acceded to, the name Proteus hauseri is herein proposed for Proteus vulgaris genomospecies 3. Its type strain is ATCC 700826T. Proteus genomospecies 4, 5 and 6 will remain unnamed until better phenotypic differentiation can be accomplished. All Proteus genomospecies were similar in their antimicrobial susceptibility patterns. Nineteen strains were isolated from urine, four from faeces, two from wounds, nine from other human sources and two from animals.